A checklist for intrahospital transport of critically ill patients improves compliance with transportation safety guidelines. Issue 1 (January 2020) - Williams, Peter; Karuppiah, Sathappan; Greentree, Kate; Darvall, Jai
Abstract: Objectives: Critically ill patients are often transferred from the intensive care unit (ICU) to other locations around the hospital during which adverse events, some life threatening, are common. An intercollegiate guideline covering the transport of critically ill patients exists in Australasia; however, compliance with this guideline has previously been shown to be poor, and its role in improving safety in transportation of patients in the ICU is unknown. We performed a pre–post interventional study in a tertiary metropolitan ICU, assessing the impact of the introduction of a transport checklist on guideline compliance. Methods: We performed a prospective, pre–post interventional study, including a total of 76 transfers of critically ill patients between August 2016 and April 2017. Results: After introduction of the checklist, aggregate median (interquartile range) guideline compliance improved from 86.7% (80.0–92.9) to 90% (86.7–100) (p = 0.01). Significant improvements were found in notification of the transport destination (83.7% vs 100%, p = 0.010) and transporting doctors' knowledge of the Cormack–Lehane grade of laryngoscopy (60.5% vs. 84.2%, p = 0.021). There was, however, a reduction in the proportion of full oxygen cylinders taken on transports (100% vs. 76.3%, p = 0.002). Conclusions: We conclude that a checklist is useful in improving safety in the transport of a critically ill patient population.